2004
DOI: 10.1620/tjem.204.179
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fasting Month of Ramadan on the Abdominal Fat Distribution: Assessment by Computed Tomography

Abstract: The aim of this study was to evaluate the changes in abdominal fat distribution in the fasting month of Ramadan. Thirty-eight healthy volunteers (17 women and 21 men) who fasted in the month of Ramadan in 2002 were included in this prospective study. Waist, hip and thigh circumferences, weight and height of all subjects were measured. Waist-to-hip ratio (WHR), waist-to-thigh ratio (WTR) and body mass index (BMI) were calculated for each subject. For assessing the fat distribution in the abdomen, computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 23 publications
6
50
0
1
Order By: Relevance
“…1 Flowchart showing the selection of studies included in the present systematic review of Ramadan fasting effects on body weight (*two studies reported the effects of Ramadan fasting in healthy and obese subjects, and in healthy and diabetic subjects) Table 1 provides detailed information on the studies used in the meta-analysis (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and descriptive statistics of their characteristics. The average number of subjects per study was 35?8 (SD 27?9) and the subjects' average age was 29?4 (SD 6?4) years old.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Flowchart showing the selection of studies included in the present systematic review of Ramadan fasting effects on body weight (*two studies reported the effects of Ramadan fasting in healthy and obese subjects, and in healthy and diabetic subjects) Table 1 provides detailed information on the studies used in the meta-analysis (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and descriptive statistics of their characteristics. The average number of subjects per study was 35?8 (SD 27?9) and the subjects' average age was 29?4 (SD 6?4) years old.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…There are studies that reported a definite loss of body weight or body fat during Ramadan (7)(8)(9)(10)(11)(12)(13) ; while there are as many studies that showed either no significant loss of body weight (14)(15)(16)(17) or a slight increase in body weight during or after Ramadan (3,(18)(19)(20) .…”
mentioning
confidence: 99%
“…The majority of Indonesian people are Muslims, who are obliged to fast (total abstinence from food and drink) for as long as 14 h (from 0330 to 1730) each day for a month. Many studies have been conducted to evaluate the impact of Ramadan fasting on various aspects of health, including lipid metabolism (Fedail et al, 1982;El Arnoaty and Johnson, 1991;Adlouni et al, 1997), acute coronary heart disease and respiratory system (Temizhan et al, 1999;Ramadan and Barac-Nieto, 2000), water balance (Duncan et al, 1990;Schmahl and Metzler, 1991;Leiper et al, 2003;Basiri et al, 2004), dietary intake, endocrine function, serum fructosamine, and clinical, anthropometrical, and most biological parameters (Habbal et al, 1998;Perk et al, 2001;Beltaifa et al, 2002;Ramadan, 2002;Gharbi et al, 2003;Gustaviani et al, 2004;Kassab et al, 2004;Yucel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…First, all of these studies focused exclusively on fasters (Fedail et al, 1982;Frost and Pirani, 1987;Hussain et al, 1987;Hallak and Nomani, 1988;Ch'ng et al, 1989;Iraki et al, 1997;Bigard et al, 1998;Perk et al, 2001;Beltaifa et al, 2002;Ramadan, 2002;Roky et al, 2004) and neglected nonfasters, who constitute an important control group. Second, because blood sampling during fasting is often regarded as intrusive, many of these studies were conducted with small sample sizes, and some studies involved gender-mixed sampling (Hussain et al, 1987;Habbal et al, 1998) or sampling after Ramadan rather than during Ramadan (Yucel et al, 2004). All of these features could produce substantial variability in the results.…”
Section: Introductionmentioning
confidence: 99%
“…Since Ramadan month is according to the lunar http://dx.doi.org/10.15218/zjms.2014.0039 817 positive effects on the body. 2 The following parameters go down during fasting: serum lipids, 3 blood sugar, 4 blood pressure (BP) 5 and body weight. 6 This study sought to investigate the effects of Ramadan fasting during summer time on the body physiology particularly in terms of body weight, blood sugar, serum lipids and BP.…”
Section: Introductionmentioning
confidence: 99%